Niekonstytucyjność odwołań do „przepisów o ruchu drogowym” w zakresie obowiązku podatkowego oraz zwolnień w podatku od środków transportowych - Szpilski, Chrystian (Studia Prawa Publicznego, 2025)
The aim of this article is to analyse the compliance of the provisions of the Local Taxes and Fees Act (hereafter: LTFA), regulating tax liability and subject exemptions in the transport vehicle tax, with the Constitution of the Republic of Poland. The study hypothesis indicates that Article 9(4b) and Article 12(1)(2) and (5) of the Act infringe Articles 84 and 217 of the Constitution by referring to non-tax statutes. The research employed the dogmatic-legal method and an analysis of the views of legal doctrine as well as the jurisprudence of the Constitutional Tribunal and administrative courts. The study discusses the constitutional requirements for the statutory form of imposing taxes and the principle of legal certainty. It identifies the imprecision of references to “road traffic regulations” and the resulting case law discrepancies and difficulties in determining the moment of tax liability. Legislative recommendations de lege ferenda are formulated to eliminate drafting defects and restore coherence to the tax system. The proposed solutions include the introduction of autonomous definitions within the LTFA and the removal of references to non-tax acts, ensuring clarity and uniform application of the law.